RTVE audiovisual archive. Programmes on the Spanish Civil War broadcasted between 1956 and 1975. - Paz, María Antonia; Montero, Julio (Revista General de Información y Documentación, 2012)
This is an account of the television programmes about the Spanish Civil War broadcasted between 1956 and 1975 which are kept at the RTVE archive, as well of the ways to access this material. Both their interest and the basic historical context in which they were produced and broadcasted are also described. The importance of newspaper archive sources in guiding the searches and in completing the flaws of archive material is also shown.